Tinjauan Yuridis Blanket Overflight Access Amerika Serikat Atas Wilayah Udara Indonesia Berdasarkan Konvensi Chicago 1944 - Fathurrahman Hadi; Aditya Tri Winata; Delon Ananda Yahya Harianja; M.Primananda A.H (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study analyzes the United States’ extensive overflight rights in Indonesian airspace under the 1944 Chicago Convention and bilateral agreements between the two countries. As a sovereign state, Indonesia possesses full and exclusive rights over its airspace as stipulated in Article 1 of the 1944 Chicago Convention. However, in practice, the United States has significant access to Indonesian airspace through bilateral aviation agreements and other diplomatic arrangements. The method used in this study is normative legal analysis employing legal, conceptual, and comparative approaches. The research findings indicate that overflight access generally does not automatically derive from the 1944 Chicago Convention and must be based on bilateral agreements that remain consistent with Indonesia’s sovereignty and the principles of international law.